Predictors of pharmacy students' performances in first year at a University of Technology in Gauteng Province : analysis using hierarchical regression models - Letsoalo, M. E; Olivier, E. (African Perspectives of Research in Teaching & Learning (APORTAL), 2023)
This cross-sectional quantitative study sought to identify factors associated with the performance of first-year pharmacy students. It made use of secondary data obtained from the Department of Pharmaceutical Sciences at Tshwane University of Technology (TUT). Even after adjusting for Grade 12 science subjects, the results of hierarchical logistic regression models show that male students were slightly less likely than female students to pass the first year of pharmacy in 2015, 2016, and 2017. Academic performance predictors could be used to reconfigure admissions criteria. As a result, a better understanding of the factors influencing pharmacy student performance may aid pharmacy educators in developing effective interventions to improve student performance. Identifying new predictors of academic performance may assist the TUT pharmacy school to retain and graduate better pharmacists. This study suggests that a similar study should be conducted using structural equation models and hierarchical regression models to confirm the current results using a data set containing other important predictors mentioned in previous studies.
Journal article published in African Perspectives of Research in Teaching & Learning (APORTAL) Vol 7 (1) (2023)
Keywords: Hierarchical logistic regression model; Pharmacy programme; Student performance; Selection criteria; Predictors; Pharmacy students; Academic achievement; College students